The Norwegian market for pharmaceuticals and the non-mandatory substitution reform of 2001: The case of enalapril - Tiziano Razzolini (University of Oslo, Department of Economics, 2004)
A new demand model which accounts for the effect of the age of drugs on pharmaceutical demand is provided. Within this framework the problem of persistence in consumption of original branded drugs and a particular case of intra-molecular substitution are analyzed. I find that interacting price with time in a logit demand structure provides intuitive patterns of substitution between branded and generic drugs and yields, with an assumption of Bertrand-Nashequilibrium on the supply side, intuitive dynamics of the mark-ups for generic manufacturers over time. The effect of a non-mandatory substitution reform introduced in Norway in March 2001 is analyzed in terms of increased sensitivity to price and is found to be negligible. The presence of competition between generic producers is also verified.
Keywords: L65; P36; 330; Generic substitution; off-patent; branded drugs; Arzneimittelmarkt; Produktsubstitution; Norwegen